Advancements in PV-thermal systems with and without phase change materials as a sustainable energy solution: energy, exergy and exergoeconomic (3E) analytic approach - Imtiaz, Ali Laghari; Mahendran, Samykano; Pandey, A. K.; K., Kadirgama; Tyagi, V. V. (Royal Society of Chemistry, 2020)
Photovoltaic thermal (PVT) systems are increasingly becoming an essential part of the solar application systems integrating the photovoltaic (PV) and solar thermal collectors into a single unit to produce heat and electrical energy from the intermittent solar irradiation. Energy systems are usually analyzed by energy and exergy analyses. Most of these systems are designed considering their energy performances based on the 1st law of thermodynamics. Generally, the energy reduction occurring in systems can be detected using exergy analysis and is a valuable tool for investigating the energy efficiency of energy systems, thereby helping the complicated thermodynamic systems more efficient. The exergoeconomic analysis is a form of economics focused on exergy analysis and is a hybrid of exergy and cost analysis to enhance the output of PVT systems. This allows designers to determine strategies to enhance the system efficiency from its cost perspective. Herein, a detailed literature review on energy, exergy and exergoeconomics (3E) analysis and their applications in air-based, water-based and bi-fluid PVT systems with and without integrated phase change materials (PCMs) is executed. It was found that water-based PVT systems with PCMs (PVT-PCM) are more feasible as the energy and exergy efficiencies are enhanced and their energy payback time reduced as compared to other conventional systems. The energy and exergy efficiencies of the water-, air- and bi-fluid-based PVT systems integrated with PCMs were found to be higher than the systems without PCM integration. PCM integration with a water-based PVT system can lead to the storage of thermal energy and also enhance the overall exergetic efficiency of the system up to 25%. The exergy efficiencies of PVT systems were found to be between 3–14%, and generally less than their energy efficiencies. Thus, 3E analysis is found to be a more technical approach to assess the performance of PVT systems and gives a complete overview of the performance of the system.